Meningkatkan Keterampilan Berbicara Bahasa Inggris untuk Layanan Makanan dan Minuman bagi Mahasiswa Pariwisata melalui Pembelajaran Kolaboratif - I Gede Astawa; I Ketut Ardiasa (Jurnal Kajian dan Terapan Pariwisata, 2022)
The collaborative learning approach has been widely used to improve the quality of learning in a variety of courses. This present study used the collaborative approach in English learning for the specific purpose of restaurant services. The research used a mixed-method. The research data were obtained from the result of pre-and post-performance tests, participant observation notes, and unstructured interview notes. There were 35 students involved as the sample and informants. The quantitative data obtained were calculated by using a t-test and the qualitative data obtained were analyzed using content analysis. The significance value (2-tailed) of the implementation of the pre-test and post-test was 0.000 (p < 0.05). Thus, the results of the pre-and post-test experienced a significant change. The students showed positive feedback toward the collaborative approach applied. Based on the findings, collaborative learning could enhance both students’ English-speaking skills and job-related skills.